Clinical and epidemiological use of nested PCR targeting the repetitive element IS1111 associated with the transposase gene from Coxiella burnetii - Mares-Guia,Maria Angélica M.M. (2018)
ABSTRACT Q fever is a worldwide zoonosis caused by Coxiella burnetii—a small obligate intracellular Gram-negative bacterium found in a variety of animals. It is transmitted to humans by inhalation of contaminated aerosols from urine, feces, milk, amniotic fluid, placenta, abortion products, wool, and rarely by ingestion of raw milk from infected animals. Nested PCR can improve the sensitivity and specificity of testing while offering a suitable amplicon size for sequencing. Serial dilutions were performed tenfold to test the limit of detection, and the result was 10× detection of C. burnetti DNA with internal nested PCR primers relative to trans-PCR. Different biological samples were tested and identified only in nested PCR. This demonstrates the efficiency and effectiveness of the primers. Of the 19 samples, which amplify the partial sequence of C. burnetii, 12 were positive by conventional PCR and nested PCR. Seven samples—five spleen tissue samples from rodents and two tick samples—were only positive in nested PCR. With these new internal primers for trans-PCR, we demonstrate that our nested PCR assay for C. burnetii can achieve better results than conventional PCR.